Uji aktivitas antioksidan dan sitotoksik ekstrak daun Jarak Pagar (Jatropha curcas) - Sudarman Rahman; Erwin Prasetya Toepak; Stevin Carolius Angga; Ysrafil Ysrafil (Politeknik Kesehatan Kemenkes Aceh, 2023)
Background: antioxidants play an important role in preventing cell damage and generating inhibition of signalling pathways of cancer, aging and various diseases. Several extracts, oils, and herbal formulations were shown to be important Antioxidant agents for preventing cell damage. Jarak Pagar (Jatropha Curcas) leaves. were a common natural Antioxidant phytochemical screening of Jatropha leaves that contained flavonoids, where flavonoids acted as antioxidants.Objectives: this study aims to determine the Antioxidant and cytotoxic activity of ethanol extract of Jatropha leaves using the DPPH and shrimp larvae method, respectively.Methods: the design in this study was quasi-experimental, using various concentrations of ethanol extract and vitamin C (comparison control) in inhibiting free radicals and each Concentration was repeated three repetitions. The research was conducted at the Laboratory of Chemistry FMIPA Palangka Raya University and Chemistry Education FKIP Halu Oleo University in 2022. The ethanol extract of Jatropha leaves weighing 60 grams was extracted using the Soxhletion method to obtain 1.667 grams of thick ethanol extract. Phytochemical characterization was further conducted by tube method, Antioxidant tests by DPPH (1,1-diphenyl-2-picrylhydrazyl) and cytotoxic test assessed by the Brine Shrimp Lethality Test (BSLT) method. The data analysis used the One Way Anova statistical test and continued with post hoc Tamhane at 95% Cl.Results: the results showed that Jatropha curcas L. leaves contained several secondary metabolites such as flavonoids, saponins, alkaloids, polyphenols and tannins. Furthermore, the Antioxidant activity test of ethanol extract of Jatropha curcas L leaves and control (vitamin C) provided IC50 of 32.83 ± 0.09 (μg/mL) and 8.78 ± 0.21 (μg/mL), respectively. Another finding found that ethanol extract of Jatropha leaves contained active compounds that were toxic to shrimp larvae with LC50 of 427 ppm. Based on the One Way Anova test, each Concentration had a significant difference in the percentage of radical scavenging (p= 0,05). The Concentration of 160 ppm is the most effective in radical scavenging.Conclusion: we concluded that the ethanol extract of Jatropha leaves showed strong Antioxidant activity and potential as an anticancer agent